The collection and understanding of administrative data in UK police forces - Keay, Scott (The crime data handbook, 2024)
This chapter explores the potential for administrative data to improve police policy and decision making by focusing on how to incorporate a critical reflection into the analysis and interpretation of administrative data by understanding its construction. To do this, we focus on Police Recorded Crime as the key source of administrative data in policing in England and Wales. We then evaluate where policing is currently in terms of understanding the need for and having the skills to undertake this critical reflection, based on work undertaken with 60 police analysts from the North of England in 2018/19 as part of the N8 Policing Research Partnership. Finally, we look to the future and raise the issue of the place of the police analysts in the policing institution, considering what they currently contribute and what they could contribute to police policy and decision making.